Training System for Professional Development (TASPOD): A System Based on Kingdom of Saudi Arabia Higher Learning Institution - Rafiza, A.R.; Idris, A.Y. (University of Malaya, 2015)
Professional development in Kingdom of Saudi Arabia is still in its infancy as there is lack of sustained and progressive PD programs. However, Saudi government has realized that it should improve the quality of human resources that the Saudi universities produce in order to improve the economy of the country. The deliverables of this research at the initial stage include the development of the system framework of the E-training for professional development. The system named Training System for Professional Development’ (TaSPoD) will be an online training system for educators in the higher learning institutions in KSA. The main purpose of the system is to enhance and equip educators competency, professionalisms, knowledge, skills and practices in an effective way; utilizing the system through 3 distinct modules; the training module, the assessment module and the management module. In designing effective training product, the design of the module adapts Merrill's First Principles of Instruction. The model emphasizes on four distinct phases of learning; (1) activation of prior experience, (2) demonstration of skills, (3) application of skills and (4) integration of these skills into real-world activities. By using TaSPoD, the continuing development program can be conducted interactively by online and can be accessed anywhere at anytime. Copyright@ 2014 University of Malaya all right reserved